Unilateral Cryptorchidism in Mice Mutant for Ptgds. Issue 2 (17th October 2012) - Philibert, Pascal; Boizet‐Bonhoure, Brigitte; Bashamboo, Anu; Paris, Françoise; Aritake, Kosuke; Urade, Yoshihiro; Leger, Juliane; Sultan, Charles; Poulat, Francis
ABSTRACT The pathophysiology of cryptorchidism, abnormal testicular descent, remains poorly understood. In this study, we show that both heterozygous and homozygous mice deficient for lipocalin‐type prostaglandin D2 (PGD2) synthase (Ptgds) presented unilateral cryptorchidism affecting the second phase of testicular descent in 16% and 24% of cases, respectively. The adult cryptorchid testes show an increase in spermatogonia apoptosis along with a global decrease in the tubule size parameters, whereas the gubernaculum of newborn mutants present some histological abnormalities. Disruption of the inguinoscrotal phase did not present impairment of the androgen pathway but rather a decrease in Rxfp2 mRNA expression in the gubernaculum. These observations led us to investigate the role of the PGD2 signaling pathway in human testicular migration through PTGDS sequencing of DNA from 29 children with cryptorchidism. However, none of the investigated cases presented mutations in the PTGDS gene. Nevertheless, our results identify the PTGDS enzyme as a novel component in the cryptorchidism puzzle.